2021
DOI: 10.3390/psychiatryint2030022
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled CBT Intervention for Maladaptive Perfectionism: Outcome and Predictors

Abstract: Maladaptive perfectionism has been associated with certain mental health problems. Moreover, studies suggest that the development of perfectionism can be attributed to childhood experiences and, more specifically, to parenting styles. (1) Background: The aims of the present study were first to examine the relationship of perfectionism to perceived parenting and current symptoms of depression and anxiety and, secondly, to study the effectiveness of a group CBT intervention program for high perfectionism; (2) Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…These results seem to corroborate the hypothesis that perfectionism is related to controlling and highly critical parenting styles, where parents are described as being demanding and imposing extremely elevated standards of performance on their children [25,26]. This association has also been reported in adulthood: a recent CBT Intervention study with young adults [30] reported that a perceived negative parenting style is associated with specific, maladaptive aspects of perfectionism.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results seem to corroborate the hypothesis that perfectionism is related to controlling and highly critical parenting styles, where parents are described as being demanding and imposing extremely elevated standards of performance on their children [25,26]. This association has also been reported in adulthood: a recent CBT Intervention study with young adults [30] reported that a perceived negative parenting style is associated with specific, maladaptive aspects of perfectionism.…”
Section: Discussionsupporting
confidence: 79%
“…While there is evidence showing a positive association between authoritarian parenting and maladaptive perfectionism [25,29,30], some studies reveal that this parenting style predicts both perfectionism facets [21,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%